House for C.B. Jones, Esq., Mount Tolmie, Victoria, B.C. - http://id.worldcat.org/fast/175028 (1913)
1911 Woodley Road, Saanich, B.C.; Plans, elevations, sections and details. Two-storey house with basement. The basement includes a play room, furnace room and fuel bin. The ground floor comprises a hall, library, living room, veranda, dining room, kitchen, pantry, two bedrooms and bathroom. A large landing and five bedrooms make up the second floor.; Item is an architectural drawing by Samuel Maclure prepared for C.B. Jones of Saanich, B.C.